Analisis Produk Biodiesel Minyak Kelapa Hasil Dari Reaktor Destilasi Pada suhu 260-290 ̊C - Leonardo Valinka; Firdaus; Azharuddin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research discusses the results of coconut oil biodiesel products using a distillation process conducted in a distillation reactor at a temperature of 260-290̊ C. Then it was tested in the lab to obtain values according to the measurement parameters, among which the product quality measurement parameters used include water content, density, cetane number, and flash point. After obtaining the results of the quality parameter tests for coconut oil biodiesel, they were compared with the biodiesel standards, and it was found that the produced biodiesel product exceeded the biodiesel standards. The average values obtained for each testing parameter are water content 3.77%, density 0.8817 gr/ml3, cetane number 65.6, and flash point 124.3̊ C.